2011
DOI: 10.1198/jcgs.2010.09004
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Inference on Random Graphs: Comparative Power Analyses via Monte Carlo

Abstract: We present a comparative power analysis, via Monte Carlo, of various graph invariants used as statistics for testing graph homogeneity versus a "chatter" alternative-the existence of a local region of excessive activity. Our results indicate that statistical inference on random graphs, even in a relatively simple setting, can be decidedly nontrivial. We find that none of the graph invariants considered is uniformly most powerful throughout our space of alternatives. Code for reproducing all the simulation resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 11 publications
2
33
0
Order By: Relevance
“…Applying these kNN classifiers to a problem of considerable scientific interest -classifying human structural MR connectomes -we find that even with a relatively small sample size (s ≥ 20), the approximately graph-matched kNN algorithm performs nearly as well as the kNN algorithm using vertex labels, and slightly better than a kNN algorithm applied to a set of graph invariants proposed previously (Pao, Coppersmith, and Priebe 2011). This suggests that the asymptotics might apply even for very small sample sizes.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Applying these kNN classifiers to a problem of considerable scientific interest -classifying human structural MR connectomes -we find that even with a relatively small sample size (s ≥ 20), the approximately graph-matched kNN algorithm performs nearly as well as the kNN algorithm using vertex labels, and slightly better than a kNN algorithm applied to a set of graph invariants proposed previously (Pao, Coppersmith, and Priebe 2011). This suggests that the asymptotics might apply even for very small sample sizes.…”
Section: Discussionmentioning
confidence: 74%
“…Specifically, letL ψ s be the misclassification rate for some classifier that operates on T s , that is, only has access to shuffled graphs. Consider the set of seven graph invariants studied in Pao, Coppersmith, and Priebe (2011): size, max degree, max eigenvalue, scan statistic, number of triangles, clustering coefficient, and average path length. Via Monte Carlo, Pao, Coppersmith, and Priebe were unable to find a uniformly most powerful graph invariant test statistic (Priebe, Coppersmith, and Rukhin 2010) for a particular hypothesis testing scenario on shuffled graphs.…”
Section: Comparing Asymptotic Performancesmentioning
confidence: 99%
“…In [9] various graph invariants (size, maximum degree, scan statistic, etc.) are considered for their power as test statistics and it is demonstrated via Monte Carlo that no single invariant is uniformly most powerful, while in [10] it is demonstrated that asymptotics can provide misleading comparative power analysis for size vs. maximum degree except for astronomically large graphs; see also [11] for a summary.…”
Section: Invariantsmentioning
confidence: 99%
“…The graph scan statistic is in fact quite powerful for some n p m s, as demonstrated in Pao et al (2011). In particular, Rukhin (2009) has shown that renders the maximum degree asymptotically inadmissible for a large portion of our parameter space.…”
Section: Resultsmentioning
confidence: 96%
“…This "graph scan statistic" warrants study for its use in inference tests for anomaly detection in random social networks (see Pao et al, 2011;Priebe, 2004;Priebe et al, 2005).…”
Section: Introductionmentioning
confidence: 99%